ANALISIS KEANEKARAGAMAN JENIS TUMBUHAN OBAT TRADISIONAL BERKASIAT UNTUK PENGOBATAN PENYAKIT SALURAN KENCING DI KECAMATAN KINTAMANI, KABUPATEN BANGLI PROVINSI BALI - Darsini, Ni Nyoman (Bumi Lestari; Vol 13 No 1 (2013), 2013)
Abstract The research has done on medicinal plants are believed to cure or treat urinary tract disorders in 15 villages of Kintamani district Bangli. Based on the results of research through the interview process with the public, traders and some interviewees ceraken Jero Balian it is known there are 47 types of plants are believed to overcome the disease urinary tract disorders. Various kinds of urinary tract disorders can be cured by 47 different herbs are-different. Of the 47 plant species are classified as rare plants, three plants namely: pule (Astolnia scholaris), purnajiwa (Euchresta horsfieldii (Lesch) Benn), and suren (Taona suroni Merr). The dominant plant organ used as medicine are the leaves (59.57%).
Keywords: Keywords: Medicinal plants; urinary tract disorder; Kintamani; herbs